Around the artistic scene of 10th Street. A pioneer creative cluster in New York City - Carrascal Pérez, María F. (REIA - Revista Europea de Investigación en Arquitectura, 2018)
Since the beginning of the fifties, 10th Street concentrated an artistic activity unprecedented in the history of the paradigmatic City of New York. A significant number of artists and their diverse ways of production were hosted in the buildings of this urban artery. While the Greenwich Village bohemia or the Coenties Slip’s artists pioneered a sporadic and spontaneous relationship with the city, this synergistic model of multiple and connected art spaces along this axis could be identified as a first creative cluster, inspiring later important phenomena such as the colonization of the South of Houston Street at the hands of the artistic counterculture. The 10th Street artists’ activity would range from singular spaces and projects, such as the Tenth Street Studio Building, to the first structures of artistic cooperatives, Tenth Street Co-ops. While showing the groundbreaking relationship between this city and its art, this article particularly investigates the architectural and cultural scene of 10th Street, which would ultimately influence the 1960s’ popular urban model of the artistic district. Moreover, the revelation of its history is intended to build the antecedents of certain contemporary intervention practices and theories that rely on culture as a way of city improvement.